Energy Consumption and Energy-Related CO2 Emissions from China’s Petrochemical Industry Based on an Environmental Input-Output Life Cycle Assessment - Lu Meng; Jalel Sager (Energies, 2017)
The fast-growing petrochemical industry is one of the largest energy consumers and emitters in China, exerting a strong impact on the national economic, energy and environmental systems. We provide a holistic picture of energy consumption and energy-related CO2 emissions from China’s petrochemical industry in 2012 through an environmental input-output life-cycle assessment (EIO-LCA). We combine two perspectives: (1) direct energy consumption and emissions, and (2) the indirect energy and emissions embodied and reallocated from other sectors in the supply chain to satisfy final demand in the petrochemical industry. Results indicate that the total of its direct and indirect energy consumption and CO2 emissions accounts for approximately 32% and 18% of China’s industrial total, respectively, exerting high “influence” and “induction” with regards to the rest of the economic sectors. Most of the petrochemical industry’s embodied energy and CO2 emissions comes from the “Production and Supply of Electric and Heat Power”. We also identified five other sectors key to China’s energy conservation and CO2 mitigation efforts due to their high influence and induction effects: “Smelting and Pressing of Ferrous Metals”, “Manufacture of Non-metallic Mineral Products”, “Smelting and Pressing of Non-ferrous Metals”, “Transport, Storage and Post”, and “Mining and Washing of Coal”. A systematic view of direct and indirect energy, environmental relationships, and the conveying effects among sectors is crucial for policymaking in China to achieve its energy and mitigation goals.